Cause of Hypothyroidism in Post Iniversal Salt Iodization era in Nepal - Pokharel, Sunil (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
Introduction: Iodine deficiency remains the most common cause of hypothyroidism worldwide, but in areas of iodine sufficiency autoimmune disease (Hashimoto’s thyroiditis) is most common. After implementation of Universal Salt Iodization (USI) to control Iodine Deficiency Disorder(IDD), Nepal is heading towards iodine sufficiency but the prevalence of clinical and subclinical hypothyroidism is still high. So this study was done to find out either chronic autoimmune thyroiditis is the cause of clinical hypothyroidism in post universal salt iodization era of Nepal by measuring Anti-TPO antibody.Method: Newly diagnosed patients with Clinical or Sub clinical hypothyroidism by thyroid function test were included in this study. Anti-TPO antibody was measured by Elisa method, Anti-TPO >34 was considered positive. All the data’s were analyzed using SPSS software.Result: In this study 1000 patients were included, male to female ratio was 5:1. 270 patients had clinical hypothyroidism among which 230(85.1%) patients had Anti-TPO antibody positive. Among 730 patients with subclinical hypothyroidism only 220(30.1%) patients had antibody positive. Our result showed that TPO antibody was positive in clinical hypothyroidism compared to subclinical hypothyroidism with statistical significance (p